Pengaruh Kepuasan Kerja, Kompensasi Finansial, dan Budaya Organisasi Terhadap Retensi Karyawan: PT Campina Ice Cream Industry Tbk - Juniar Hafiz, Andy; Ubaidillah, Hasan; Andriani , Dewi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of job satisfaction, financial compensation, and organizational culture on employee retention at PT Campina Ice Cream Industry Tbk. The research method uses a quantitative approach with data collection techniques through questionnaires distributed to 145 randomly selected respondents. Data were analyzed using multiple linear regression to test the relationship between the variables studied. The results showed that job satisfaction, financial compensation, and organizational culture have a positive and significant influence on employee retention, both partially and simultaneously. Financial compensation is the most dominant variable in influencing employee retention, followed by job satisfaction and organizational culture. Simultaneously, the three variables explain 90.7% of the variation in employee retention, while the rest is influenced by other factors.